(untitled) (Medical Forum Monthly, 2023)
Objective: To compare the umbilical cord separation time with alcohol application and dry cord care in newborn Study Design: comparative study Place and Duration of Study: This study was conducted at the Pediatric Department Margalla Hospital Taxila from August 2021 to January 2022. Materials and Methods: 60 neonates were included in each DCC (dry cord care) group and alcohol group (70% alcohol). The duration of umbilical separation and the presence of umbilical local infection were observed in all neonates. SPSS version 20 was used for analysis of data. Results: The mean (±SD) cord detachment time in DCC group was 7(±1) days while in alcohol group, mean (±SD) cord detachment time was 16(±1) days. This difference between the two group was significant statistically (p=0.021). Cord infection was not observed in both the groups. 52 (86.67%) mothers were satisfied from the dry cord care method while only 28 (46.67%) mothers were satisfied from 70% alcohol method (p=0.001). Conclusion: Our study concludes that in comparison to the 70 % Alcohol approach, dry cord care was highly beneficial in healing of umbilical cord stump, reducing the risk of cord infection, and reducing the duration of cord detachment.